Synthesis and Biological Evaluation of Imidazole-2-thione Fused Furazan as a New Biheterocyclic Scaffold - Gülşah Kurt; Fatih Sevgi (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
A new imidazole-2-thione fused furazan biheterocyclic group was synthesized and its biological activity was investigated. Nitrogen rich heterocycles, imidazole-2-thione and 1,2,5-oxadiazole (furazan) have been conveni ently fused. To accomplish this, we have improved a new strategy that silica gel supported solvent free micro wave dehydration of vicinal dioximes. The target furazan "N,N’-diphenyl-4H-imidazo[4,5-c]furazan-5(6H) –thio ne" [II] (DFTFrz) was obtained from (4E,5Z)-4,5-bis(hydroxyimino)-N,N’-diphenylimidazolidine-2-thione [I] (DFTD) with acceptable yield and characterized by LC-MS/MS, FT-IR and NMR spectroscopy. The biological evaluation of the obtained thiourea furazan and its precursor dioxime were investigated by antibacterial effect studies using broth microdilution and disc diffusion methods. It was observed that thioure furazan was more effective on the tested pathogenic bacteria than its precursor dioxime. The compounds did not show any effect on gram negative bacteria, while they exhibited a moderate effect on gram positive bacteria, especially Staphylococcus spp.